2021
DOI: 10.7150/ijms.47339
|View full text |Cite
|
Sign up to set email alerts
|

Integrated bioinformatics analysis for differentially expressed genes and signaling pathways identification in gastric cancer

Abstract: Background: Gastric cancer (GC) has a high mortality rate in cancer-related deaths worldwide. Currently, the pathogenesis of gastric cancer progression remains unclear. Here, we identified several vital candidate genes related to gastric cancer development and revealed the potential pathogenic mechanisms using integrated bioinformatics analysis. Methods: Two microarray datasets from Gene Expression Omnibus (GEO) database integrated. Limma package was used to analyze differentially expressed genes (DEGs) betwee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…A c c e p t e d A r t i c l e analysis using the DAVID database (https://david.ncifcrf.gov/tools.jsp) [18], a widely recognized platform for high-throughput gene function analysis. Again, the organism was specified as "Sus scrofa," and we adhered to the default settings for the other parameters.…”
Section: Subsequently We Performed Kyoto Encyclopedia Of Genes and Ge...mentioning
confidence: 99%
See 1 more Smart Citation
“…A c c e p t e d A r t i c l e analysis using the DAVID database (https://david.ncifcrf.gov/tools.jsp) [18], a widely recognized platform for high-throughput gene function analysis. Again, the organism was specified as "Sus scrofa," and we adhered to the default settings for the other parameters.…”
Section: Subsequently We Performed Kyoto Encyclopedia Of Genes and Ge...mentioning
confidence: 99%
“…This was achieved using the g:Profiler tool (available at https://biit.cs.ut.ee/gprofiler/orth) [17]; the organism was set to "Sus scrofa", the statistical domain scope was set to "only annotated genes", the significance threshold was set to "Benjamini-Hochberg FDR" , and the user threshold was set to "0.05". Furthermore, we performed a KEGG pathway analysis using the DAVID database (https://david.ncifcrf.gov/tools.jsp) [18]. For this analysis, the organism was again set to "Sus scrofa", and the default settings were maintained for other parameters.…”
Section: Functional Enrichment Analysis Of Overlapping Depsmentioning
confidence: 99%
“…Genes that correspond to multiple probes should all be selected for the average expression value of that gene. We normalized the matrix data and removed the batch effect using the "limma" and "sva" packages in R [27][28][29]. Besides, 1495 OS-related genes (Relevance score > 5) were obtained from the GeneCards database.…”
Section: Data Collectionmentioning
confidence: 99%
“…At present, many bioinformatic studies about GC have been published, but the differentially expressed genes (DEGs) and signaling pathways revealed by different studies were not consistent. The study by Yang and Gong (2021) showed that OLFM4, IGF2BP3, CLDN1, and MMP1 were the most significantly upregulated DEGs, which significantly enriched in negative regulation of growth, fatty acid binding, and cellular response to zinc ions. In a bioinformatics analysis conducted by Xu et al (2021), the expressions of ITGB1 and alpha-2 collagen type I (COL1A2) were significantly increased in GC tissues, and 63 characteristic DEGs were mainly involved in regulating extracellular matrix (ECM)-receptor interactions and the PI3K-Akt signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Most published experimental and bioinformatic studies included GC specimens with unclear tumor stages, making it impossible to accurately analyze the DEGs and signaling pathways throughout GC development (Yang et al, 2021;Xu et al, 2021). In this study, therefore, we retrieved three microarray datasets containing gene data with definite GC stages and then divided them into the early stage (ES) group and the late stage (LS) group.…”
Section: Introductionmentioning
confidence: 99%